Study of hygrothermal comfort conditions and habitability intwo dwellingsof theSocio Vivienda1program,Guayaquil - Dick Zambrano , Santiago Raymundo; González Burneo, Vicente; Palacios Portes, Carlos (Revista Universidad de Guayaquil, 2016)
The hygrothermal comfort conditions offered by the one-storey houses built by the government in the housing program Socio Vivienda 1(PHSV1G), motivated the authors to investigate the reasons why indoor temperature is higher than outdoor temperature. Therefore, this study aims to diagnose the hygrothermal comfort degree by convection and conduction, and its causes, in two PHSV1G houses with different orientation. The purpose is to offer a tool, which may improve future housing construction projects, optimize the habitability and comfort conditions of the inhabitants, and contribute to energy saving. Likewise, the intention is to prevent such houses from permanent energy demand, in order to ventilate or climatize every engaged environment, without affecting the inhabitants’ monthly invoicing. Finally, this article will contribute to save the energy subsidized by the government, which over time, could imply to the government an expense greater than housing cost. Hence, an investigation guide in the axes of comfort and technology was established, allowing to become acquainted of the several causes that contribute to temperature increase, through hygrothermal thermometers and anemometers measurements, as well as the use of the DesignBuilder energy simulation software.